Ethological Aspects of Honeybee Apis mellifera (Hymenoptera, Apidae), Adaptation to Parasitic Mite Varroa destructor (Mesostigmata, Varroidae) Invasion - Akimov, I.A.; Kiryushyn, V.E. (Вестник зоологии, 2010)
Some ethological aspects of A. mellifera Linnaeus, 1758 (Hymenoptera, Apidae), adaptation to parasiting the mite V. destructor Anderson et Trueman (Mesostigmata, Varroidae) are shown. The basic complexes of behaviour reactions, directed on a fight against the parasitic mites of bees brood at the genus Apis are shown, their comparative efficiency under various conditions and evolutional perspective. Possibility of ethological adaptation of honey bee to V. destructor parasiting, direction of selection by this sign and influencing of human on parasitic-host system was discussed. An approach to the selection of bees with the purpose of resistanse to varroosis promoution is proposed. В статье освещаются некоторые этологические аспекты адаптации медоносной пчелы Apis mellifera Linnaeus, 1758 (Hymenoptera, Apidae) к паразитированию на ней клеща Varroa destructor Anderson et Trueman (Mesostigmata, Varroidae). Показаны основные комплексы поведенческих реакций, направленных на борьбу с клещами-паразитами расплода у пчел рода Apis, их сравнительная эффективность в различных условиях и эволюционная перспективность. Обсуждается возможность этологической адаптации медоносной пчелы к варроа, направленность отбора по этому признаку и влияние человека на данную паразито-хозяинную систему. Предложен подход к селекции пчел с целью повышения устойчивости к варроозу.